Organizational skills development: the context of information technologies - Pereira de Moraes, Carlos Alexandre; Bezerra Pimentel, Leonardo; Esteves Lattanzi, Iasmim (Brazilian Journal of Operations & Production Management, 2018)
The objective is to discuss the notions of Cyberculture in institutional teaching-learning practices articulated to other important contemporary concepts, coming from the great area of sociology, with a view to positioning the guiding questions of social engagement in teaching-learning practices. In this way, it aims to support in this approach the pertinent perspective of social engagement associated with the plurality of the different socioeconomic contexts in which formal education is carried out. In this sense, the political and economic context that constitutes the teaching practice in the undergraduate courses of the Brazilian universities and their unfolding in the teaching practices is emphasized. In this sense, the political and economic contexts that constitute the teaching practice in the undergraduate courses of the Brazilian universities and their unfolding in the teaching practices is emphasized.